Sikap Ikhtiar Orang Tua terhadap Perilaku Anak Berkebutuhan Khusus di Desa Kali Blau: (Studi Kasus Kecamatan Teluk Betung Bandar Lampung) - Wulan Haryati; Agung M. Iqbal; Nesia Mu’asyara (Pusat Riset dan Inovasi Nasional, 2024)
This research is motivated by the phenomenon of low assessments of other people towards children with special needs (ABK), because children with special needs (ABK) have differences from children in general.And requires special handling according to developmental disorders and differences that are possessed, cognitive, speech, vision, hearing, social and emotional. Parents must have the ability to handle their child's life processes more optimally. The goal of the endeavor itself is an effort or effort in order to achieve everything that is desired or desired in life,With the attitude of parents' efforts towards the behavior of children with special needs, this can be the best way for children to be well accepted in their surroundings. The method used is descriptive qualitative with data collection through observation, in-depth interviews, and questionnaires.